A Quantum Chemistry Approach of Breast Cancer Drugs Bound to Human Serum Albumin. Issue 5 (24th February 2022) - Tavares, Ana Beatriz M.L.A.; Albuquerque, Eudenilson L.
Abstract: The bindings of three different anticancer drugs, Cu(BpT)Br (2‐benzoylpyridine thiosemicarbazone copper), NAMI‐A (imidazolium trans‐imidazoledimethylsulphoxide‐tetrachlorido ruthenate), and DOX (doxorubicin), widely used in the breast cancer treatment, to human serum albumin (HSA) are investigated using a quantum chemistry approach based on the density functional theory calculations employing a dispersion corrected exchange‐correlation functional within a fragmentation strategy. As a consequence, it is possible to identify the magnitude of the most relevant quantum binding interactions of these supramolecular complexes, and thus guide their molecular modification process. The data obtained in this work highlight the power of quantum calculations as an important tool for the drug design process, and pave the way for the use of HSA‐ligand interactions during the rational design of new anticancer compounds. More important, the results show that HSA/multi‐drug complex, formed by the combination of the three individual anticancer drugs [Cu(BpT)Br]–(NAMI‐A)–(DOX), increases the targeting ability compared with each single drug's interaction with HSA, in agreement with in vivo predictions. Abstract : A quantum chemistry simulation is used to quantify the most relevant residues' binding energies of three breast's anticancer drugs in complex with the human serum albumin HSA, namely Cu(BpT)Br, NAMI‐A, and DOX. For comparison, the binding energy of the HSA/multi‐drug complex, formed by the combination of the three individual anticancer drugs, is also presented and its main features discussed.